Sistem Pemantauan Infus Berbasis IoT dengan Notifikasi Real-Time Melalui Telegram - Teodora Fenny Aliansih; Rahmi Hidayati; Kartika Sari (Jurnal PROCESSOR, 2024)
Infusions are clinical equipment for administering liquid medication or nutrients to patients. Infusion fluid is stored in a sterile bag and delivered to a vein through a tube. Infusion monitoring is usually done manually by nurses, which often results in negligence such as replacing the liquid run out too late, handling infusions that are not dripping, and dealing with blood that rises into the infusion hose. Therefore, a real-time monitoring system is needed that can provide information and remote notifications about the condition of the infusion. This research develops an IoT-based system using NodeMCU ESP32, Loadcell sensor, TCRT5000 sensor, LDR sensor, Node-RED, and Telegram bot application. NodeMCU ESP32 serves as the main controller. Loadcell sensor gauges volume of the infusion fluid, TCRT5000 sensor counts droplets per minute, and LDR sensor detects blood in the infusion hose. Sensor data is sent to Node-RED for processing and display on the Telegram bot application. The accuracy of the Loadcell sensor reaches 95.69%, while the TCRT5000 sensor has an accuracy of 76.73%. Notifications are sent when the infusion fluid volume is less than 100 ml, the infusion fluid is not dripping, and when the LDR sensor detects blood in the infusion hose.